On the relation between measures defining the Stieltjes and the inverted Stieltjes functions - Gilewicz, J.; Pindor, M. (Український математичний журнал, 2010)
A compact formula is found for the measure of the inverted Stieltjes function expressed by the measure of the original Stieltjes function.